THE EFFECT OF BRAND IMAGE ON CUSTOMER LOYALTY AT AROMA BAKERY & CAKE SHOP JL JENDERAL ABDUL HARIS NO 31 BC MEDAN JOHOR - Yuniarti Harahap (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
This study entitled